کەرەستە مۆرفۆلۆژییەکانی کات لە زمانی کوردیدا - خۆشناو, پ.ی.د.شێروان حوسێن; محمود, سومەیە علی (Sulaimani Journal for Humanities, 2023)
This study makes an attempt to explore the morphological units of time in Kurdish. In language, time concept can be designated in various ways and means. This is because expressing the concept of time is a necessity of language speakers. When morphological units are separated from each other, each has the function of conveying a concept or meaning. The present study explores the morphological units that have exposed the concept of time; some of them are words, and some others are bound morphemes. Words belong to different categories such as nouns and adverbials. Additionally, bound morphemes are either grammatical or lexical bound. They are the products of each of these different classes of words and morphemes signifying specific concepts and the extent of each of them in Kurdish based on Kurdish dictionaries and Kurdish speech.
Keywords: time; morphology; morphological units; bound morpheme; tense